2020
DOI: 10.3390/nano10122553
|View full text |Cite
|
Sign up to set email alerts
|

Role of Thermodynamics and Kinetics in the Composition of Ternary III-V Nanowires

Abstract: We explain the composition of ternary nanowires nucleating from a quaternary liquid melt. The model we derive describes the evolution of the solid composition from the nucleated-limited composition to the kinetic one. The effect of the growth temperature, group V concentration and Au/III concentration ratio on the solid-liquid dependence is studied. It has been shown that the solid composition increases with increasing temperature and Au concentration in the droplet at the fixed In/Ga concentration ratio. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 35 publications
(70 reference statements)
0
36
0
Order By: Relevance
“…In spite of the lack of justification for its application for solids 51 it remains very popular for modelling vapor-liquid-solid nucleation due to its simplicity. 14,24,31 The curve (iii) corresponds to the intermediate case calculated at δ = 0.5. Finally, a non-linear case can be considered within the convex model (iv) calculated at α = 1, while the curve coincides with the Vegard's law case at α = 0.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In spite of the lack of justification for its application for solids 51 it remains very popular for modelling vapor-liquid-solid nucleation due to its simplicity. 14,24,31 The curve (iii) corresponds to the intermediate case calculated at δ = 0.5. Finally, a non-linear case can be considered within the convex model (iv) calculated at α = 1, while the curve coincides with the Vegard's law case at α = 0.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Despite a number of experimental investigations on the growth of nanowires with composition inside the miscibility gap, 21,22 the suppression mechanism in these nanostructures remain unclear. Some kinetic theories 23,24 assume that the miscibility gap might shrink under relatively high supersaturations in the liquid. Indeed, it has been shown that high concentrations of group V elements in the droplet can "straighten" the initially S-shaped liquid-solid composition dependence curve.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Full details of the model are given in the Supporting Information (SI 1: Details about the model); here we present a summary of the important features of the model and compare them to experimental data. We base our model on another very recently published model, 22 which is kinetically limited at its core and in which the composition of the growing nanowire is determined by the relative rates of attachment of InAs and GaAs to a supercritical nucleus of a certain size. The model also, however, considers thermodynamics to determine, for example, the initial nucleus composition.…”
mentioning
confidence: 99%